PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD INPRES 12/79 POLEWALI - Muhammad Amran; A. Etisya Tropy; Abd Kadir. A (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This research is a classroom action research that aims to find out how the use of audio visual media to improve students' science learning outcomes.. Data analysis techniques in this study are reducing data, describing data and drawing conclusions. Based on the results of the research in the first cycle, the teacher did not provide guidance to students so that they did not dare to express their opinion. The results of the observation of the first cycle of the first meeting and the second meeting found that 9 out of 16 students got a complete score (56.25%) and 7 people out of 16 students (43.75%)) who got an incomplete score so that based on the completeness obtained it was still are in the sufficient category. Meanwhile, in cycle II, students have the courage to express their opinions and ask questions that are still not understood in relation to the material. In the second cycle of the first and second meetings, it was found that 13 out of 16 students (81.25%) got a complete score and 3 out of 16 students (18.75%) who got an incomplete score in the good category indicating the learning objectives were achieved by Thus, the use of Audio Visual media can improve students' science learning outcomes.